Human Security and the Israel-Palestine Conflict: External vs. Internal Perspectives (Journal of International Studies, 2020)
The formation of the State of Israel in 1948 has led to bloody course of events, which continues to this day, as to who has the right to claim the land home; the Palestinian-Arabs (mostly Muslim) or the Jewish (mostly non-Arab residents). The Israel-Palestine conflict is one of the most violent and bloodiest protracted conflict in the post World War II era, which has resulted in massive human casualties and human rights abuses for decades. The numerous wars in conjunction with the rise of militant groups like Hezbollah and Hamas have led to the development of a human security dilemma in Palestine and Israel. Decades of violence and destruction have resulted in massive human casualties, political chaos and disruption to the way of life of the people in the region. The concept of human security began to enter mainstream human rights, security and international politics debate, more prominently, after the release of the 1994 report United Nations Development Programme (UNDP) report on Human Development. The report is essentially explicit manifestations of the human rights principles enshrined in the 1948 United Nations Declaration of Humans Rights (UNDHR). Human security pushes for intense promotion and greater respect for human life in all spheres of human endeavors. This article inspects the human security dimension present in the Israel-Palestine conflict. This article encompasses two major parts. The first part provides an external understanding of how human security principles can be applied to Israel- Palestine conflict and how it affects the possibility of peace. Secondly, the article addresses the question on how people ‘inside’ the conflict view human security and the possibility of peace.